Health‐economic analysis of real‐time continuous glucose monitoring in people with Type 1 diabetes. Issue 5 (6th January 2015) - Roze, S.; Saunders, R.; Brandt, A.‐S.; de Portu, S.; Papo, N. L.; Jendle, J.
Abstract: Aim: To evaluate the clinical benefits and cost‐effectiveness of the sensor‐augmented pump compared with self–monitoring of plasma glucose plus continuous subcutaneous insulin infusion in people with Type 1 diabetes. Methods: The CORE Diabetes Model was used to simulate disease progression in a cohort of people with baseline characteristics taken from a published meta‐analysis. Direct and indirect costs for 2010–2011 were calculated from a societal payer perspective, with cost‐effectiveness calculated over the patient's lifetime. Discount rates of 3% per annum were applied to the costs and the clinical outcomes. Results: Use of the sensor‐augmented pump was associated with an increase in mean discounted, quality–adjusted life expectancy of 0.76 quality–adjusted life years compared with continuous subcutaneous insulin infusion (13.05 ± 0.12 quality–adjusted life years vs 12.29 ± 0.12 quality–adjusted life years, respectively). Undiscounted life expectancy increased by 1.03 years for the sensor‐augmented pump compared with continuous subcutaneous insulin infusion. In addition, the onset of complications was delayed (by a mean of 1.15 years) with use of the sensor‐augmented pump. This analysis resulted in an incremental cost–effectiveness ratio of 367, 571 SEK per quality–adjusted life year gained with the sensor‐augmented pump. The additional treatment costs related to the use of the sensor‐augmented pump were partially offset by the savings attributable to the reduction in diabetes‐related complications and the lower frequency of self‐monitoring of plasma glucose. Conclusions: Analysis using the CORE Diabetes Model showed that improvements in glycaemic control associated with sensor‐augmented pump use led to a reduced incidence of diabetes‐related complications and a longer life expectancy. Use of the sensor‐augmented pump was associated with an incremental cost–effectiveness ratio of 367, 571 SEK per quality–adjusted life year gained, which is likely to represent good value for money in the treatment of Type 1 diabetes in Sweden. What's new?: This study builds on a recent meta‐analysis to provide further insights into the clinical and safety aspects of real‐time continuous glucose monitoring. Simulations of disease progression show how these aspects translate into long‐term patient benefits and healthcare costs. Simulations indicate that continuous glucose monitoring leads to later onset and reduced incidence of acute and long‐term diabetes‐related complications. The findings may have an important influence on informing treatment choices with respect to providing value both for patients and healthcare payers.